Aqueous charge injection: solvation bonding dynamics, molecular nonbond interactions, and extraordinary solute capabilities - Sun, Chang Q. (International reviews in physical chemistry, 2018)
Aqueous charge injection in forms of electrons, protons, lone pairs, ions, and molecular dipoles by solvation is ubiquitously important to our health and life. Pursuing fine-resolution detection and consistent insight into solvation dynamics and solute capabilities has become an increasingly active subject. This treatise shows that charge injection by solvation mediates the O:H-O bonding network and properties of a solution through O:H formation, H↔H fragilization, O:⇔:O compression, electrostatic polarization, H 2 O dipolar shielding, solute-solute interaction, and undercoordinated H-O bond contraction. A combination of the hydrogen bond (O:H-O or HB with ':' being the electron lone pairs of oxygen) cooperativity notion and the differential phonon spectrometrics (DPS) has enabled quantitative information on the following: (i) the number fraction and phonon stiffness of HBs transiting from the mode of ordinary water to hydration; (ii) solute-solvent and solute-solute molecular nonbond interactions; and (iii) interdependence of skin stress, solution viscosity, molecular diffusivity, solvation thermodynamics, and critical pressures and temperatures for phase transitions. An examination of solvation dynamics has clarified the following: (i) the excessive protons create the H↔H or anti-HB point breaker to disrupt the acidic solution network and surface stress. (ii) The excessive lone pairs generate the O:⇔:O or super-HB point compressor to shorten the O:H nonbond but lengthen the H-O bond in H 2 O 2 and basic solutions; yet, bond-order-deficiency shortens and stiffens the H-O bond due H 2 O 2 and OH − solutes. (iii) Ions serve each as a charge center that aligns, clusters, stretches, and polarizes their neighboring HBs to form hydration shells. (iv) Solvation of alcohols, aldehydes, complex salts, carboxylic and formic acids, glycine, and sugars distorts the solute-solvent interface structures with the involvement of the anti-HB or the super-HB. Extending the knowledge and strategies to catalysis, solution-protein, drug-cell, liquid-solid, colloid-matrix interactions and molecular crystals would be even more fascinating and rewarding.